Hypovitaminosis D Is Associated with Some Metabolic Indices in Gestational Diabetes Mellitus - Ayobola Abimbola Sonuga; Oyebola Oluwagbemiga Sonuga (Biomedicine Hub, 2020)
Background: Gestational diabetes mellitus (GDM), a pregnancy complication, is defined as any degree of glucose intolerance with onset or first recognition during pregnancy. Vitamin D deficiency and insufficiency has recently been recognized as a contributing factor to the pathogenesis of GDM, and this link might be associated with hyperglycemia, insulin resistance, and inflammation, which are implicated in GDM. Objectives: This study aims at investigating the relationship between vitamin D, fasting plasma glucose (FPG), insulin, zinc, ferritin, and high-sensitivity C-reactive protein (CRP) in GDM. Method: A case-control study in which 80 women attending the antenatal clinic of University College Hospital (UCH), Ibadan, Nigeria, were recruited; the women were grouped into controls (40 nondiabetic pregnant women) and cases (40 pregnant women with GDM). Blood samples were taken at the second trimester, and metabolites were quantified by standard laboratory methods. Student’s t test and Pearson correlation were used to compare variables and determine the relationship between variables, respectively. Results: Results showed significant (p < 0.05) low levels of serum vitamin D and zinc, and significant (p < 0.05) higher levels of FPG and serum insulin, ferritin, and CRP in the GDM group compared to the control group. In the GDM group, a positive weak relationship was observed between vitamin D and zinc (r = 0.18, p < 0.05), while vitamin D was inversely correlated with FPG, serum insulin, ferritin, and CRP (r = –0.23, –0.21, –0.20, –0.46, respectively, p < 0.05). Conclusion: This study suggests that hypovitaminosis D might be associated with glucose intolerance, insulin insensitivity, and inflammation, which are factors implicated in the development and progression of GDM.